Randomised, controlled trial of nasal continuous positive airway pressure in the extubation of infants weighing 600 to 1250 g. Issue 1 (1st July 1998) - Davis, Peter; Jankov, Robert; Doyle, Lex; Henschke, Philip
Abstract : AIM: To determine whether extubation to nasal continuous airway pressure (NCPAP) results in a greater proportion of infants remaining free of additional ventilatory support for one week after extubation compared with those extubated directly to headbox oxygen. METHODS: A randomised, controlled, clinical trial was conducted at the neonatal intensive care unit of the Royal Women's Hospital, Melbourne, of infants with birthweights between 600 and 1250 g, ventilated via an endotracheal tube for more than 12 hours, requiring less than 50% oxygen, a ventilator rate ⩽ 20/minute, considered by the clinical management team to be ready for extubation. Infants were randomly allocated either to NCPAP or to oxygen administered via a headbox. Success was defined by no requirement for additional ventilatory support over the week following extubation. Failure criteria were (i) apnoea; (ii) absolute increase in oxygen requirement greater than 15% above that required before extubation; or (iii) respiratory acidosis (pH<7.25 with pCO2 >6.67 kPa). RESULTS: Thirty one of 47 (66%) infants were successfully extubated to NCPAP compared with 18 of 45 (40%) for headbox oxygen. The increase in failure rate in the headbox group was due primarily to increased oxygen requirements in this group. Of the 27 who failed headbox oxygen, 26 were given a trial of NCPAP and 13 did not require endotracheal reintubation. There was no significant difference between the groups in the total number of days of assisted ventilation or the duration of inpatient stay. CONCLUSIONS: NCPAP applied prophylactically after endotracheal extubation reduces the incidence of adverse clinical events that lead to failure of extubation in the seven days after extubation. This reduction is clinically important. The benefits of NCPAP do not seem to be associated with an increased incidence of unwanted side effects.